The Implementation of AKHLAK Core Values in the Organizational Culture of PT. Sinergi Gula Nusantara PG. Djombang Baru Company - Sa'diyah, Siti Nurhalimatus; Maryati, Wiwik (International Journal of Management and Business, 2024)
The aim of this research is to increase students' insight, knowledge and skills through direct work experience in related agencies. The author's method of collecting data from fieldwork lectures is by interviewing related parties, namely direct interviews with HR staff as well as managers of AKHLAK Core Values ​​in PG. Djombang Baru and directly observe and carry out activities carried out by employees PG. Djombang Baru is a subsidiary of PT. SGN whose address is in Surabaya. PT SGN is included in the BUMN, which has established an organizational culture that must be implemented by all companies, including PG. New Djombang. This culture is known as core values, namely the principles or beliefs that form the basis of the ethics and behavior of an organization. To realize AKHLAK Core Values in the company's organizational culture, it is necessary to conduct socialization of AKHLAK Core values to all employees, Utilization of Moral Values for employees, Provide reward programs or incentives for employees, Maximizing a good and clear organizational culture by encouraging active participation in organizational culture activities, such as training, workshops, or social events, Improve corporate management governance based on consumer needs, Providing Corporate Social Responsibility funds to the community for social and economic empowerment programs, Optimizing the development of cultural awareness, and also Establish a communication forum between employees